Professional Issues in Software Engineering - Bott, Frank (CRC Press, 2001)
Software engineers are increasingly becoming business people; Professional Issues in Software Engineering, 3rd Edition gives them comprehensive coverage of the issues they should know about. While most books look at programs related to software engineering rather than the context in which they are used, this book covers the major developments that have occured in recent years, such as the Internet, Data Protection Act, and changes to the legal status of software engineers. This updated edition of a successful textbook is for undergraduate and graduate students as well as for professionals in software engineering and computer science.